Advanced sperm tests and impact on clinical male factor management. Issue 1 (18th January 2023) - Nam, Catherine S.; Mehta, Akanksha
Abstract : Purpose of review: Although semen analysis remains a cornerstone of male fertility evaluation, conventional semen analysis parameters do not assess for DNA integrity or functional capacity of sperm. Sperm DNA fragmentation (SDF) and sperm aneuploidy tests have been utilized as adjunct tools to distinguish fertile and infertile men and predict pregnancy outcomes. This review serves as an update on indications and utility of advanced sperm tests, as well as associated controversies and limitations. Recent findings: Elevated SDF is associated with prolonged time to pregnancy, lower chance of spontaneous pregnancy, and lower live birth rates. Sperm aneuploidy is more frequent in infertile men, in male partners of couples experiencing recurrent pregnancy loss, and recurrent failure of assisted reproductive technology (ART). These tests can, therefore, provide important information to guide management and counseling of infertile couples to optimize reproductive outcomes. Summary: We evaluated data surrounding SDF and sperm aneuploidy tests, which are utilized both within and beyond the scope of AUA/ASRM guidelines. While the tests at hand require further standardization and randomized controlled studies, the current data suggest strong associations with pregnancy outcomes and can be utilized to counsel and manage infertile males.